Forty signs of rain - Robinson, Kim Stanley 1952- (Bantam Books, 2004)
Two married scientists teach a Buddhist delegation from South Asia the intricacies of dealing with politicians in Washington while observing signs of an approaching catastrophe from global warming.
Keywords: Business intelligence -- Fiction; Legislators -- Fiction; Scientists -- Fiction; Suspense fiction.; Washington (D.C.) -- Fiction; Political fiction; Science fiction; Spy stories